(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Evangelical activism has used moral repertoires to legitimize or delegitimize nationwide political processes, capitalizing on conservatism anchored in all social strata. The gender approach, the recognition of diverse sexualities and the democratization of rights to marginalized groups have become major annoyances for leaders of the largest Pentecostal and Neo-Pentecostal churches, who see in these issues a great risk for the maintenance of the traditional family, but at the same time, one of the resources to be used in electoral environments, with greater or lesser adherence, according to the interests of the moment. The Colombian plebiscite for peace became one of the scenarios that made the intersectionality between politics, religion, and gender widely visible as one of the cases, among many, in Latin America.